Choline chloride-based carbon capture material and preparation method thereof

By adjusting its concentration to change the structure of the carbon-based materials based on choline chloride, the problem of poor performance of existing carbon-based materials during CO2 capture is solved, and the high-efficiency and low-energy consumption of CO2 adsorption effect is achieved.

CN119680523AActive Publication Date: 2025-03-25CHANGZHOU UNIV

Patent Information

Application Number
CN202510159243.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-25
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The existing carbon-based materials cannot perform optimally during CO2 capture, and the high-concentration CO2 capture technology has high energy consumption and high cost.

Method used

The carbon capture material based on choline chloride is used to change the structure of the material by adjusting the concentration of choline chloride, thereby improving the adsorption performance of CO2. The material forms a MIL-101 (Cr) structure with high adsorption capacity and selectivity by specific preparation methods, including ultrasonic oscillation and heat treatment.

Benefits of technology

Highly efficient adsorption of CO2 was achieved. With the increase of choline chloride concentration, the CO2 adsorption amount changed volcanically, and the CO2 adsorption amount of 0.075-ChCl-MIL-101 (Cr) was the best, and the thermal stability and adsorption performance of the material were significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680523A_ABST
    Figure CN119680523A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon capture materials, in particular to a choline chloride-based carbon capture material and a preparation method thereof. The preparation method comprises the following steps: dissolving terephthalic acid in water, adding choline chloride with different concentrations, uniformly stirring, adding chromic nitrate, oscillating in an ultrasonic oscillator for 30 minutes, dropwise adding hydrofluoric acid with the concentration of 40% while stirring, adding reactants into a reaction kettle, and reacting at 220 DEG C for 8 hours to obtain the choline chloride-based carbon capture material n-CHCl-MIL-101 (Cr). According to the invention, the influence of the concentration of choline chloride on the material structure and CO2 adsorption performance is researched, and the result shows that the change trend of the CO2 adsorption capacity is volcanic along with the increase of the concentration of choline chloride, the CO2 adsorption capacity of 0.075-ChCl-MIL-101 (Cr) is optimal, and the unique pore cage structure of MIL-101 (Cr) can well adsorb CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon capture materials, and in particular to a choline chloride-based carbon capture material and a preparation method thereof. Background Art

[0002] Along with the process of industrialization, greenhouse gas emissions, mainly carbon dioxide, have caused global warming, seriously threatening the development of human society. 2 Capture is one of the important technologies to solve the above problems. 2 There are four application scenarios for CO capture: pre-combustion capture, oxygen-enriched combustion, post-combustion capture, and direct air capture. 2 The concentrations are 15% to 60%, 75% to 90%, 4% to 15% and 0.02% to 0.04% respectively.

[0003] Currently, for high concentrations of CO 2 In the capture scenario, absorption is the most widely used decarbonization technology, in which the core materials are inorganic alkali or organic amine solution, but this technology has prominent problems such as high regeneration energy consumption and corrosion of pipelines, resulting in high decarbonization costs. In recent years, the adsorption method has been widely favored due to its high overall stability and low regeneration energy consumption, especially in low concentration (≤15%) CO 2 In the field of CO capture, it is considered to be a new generation of CO with great application prospects. 2 Capture technology, the core of the adsorption method lies in the development of adsorption materials with high adsorption capacity, high adsorption selectivity and high stability.

[0004] Commonly used adsorption materials include carbon-based materials, zeolites, silica and MOFs porous adsorption materials. Among them, MOFs materials have high crystallinity, high specific surface area and adjustable pore structure. 2 However, the existing carbon-based materials can only be used as carbon capture materials according to the physical structural characteristics of the materials, such as the pores of the materials. 2 Capture, this method cannot bring out the best capture performance of the material. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a carbon capture material based on choline chloride, so as to obtain a carbon capture material capable of obtaining better capture performance.

[0006] To achieve the above object, the present invention provides the following technical scheme: a method for preparing a carbon capture material based on choline chloride is as follows: 0.996 g of terephthalic acid is dissolved in water, choline chloride of different concentrations is added and stirred evenly, and then 2.4 g of chromium nitrate is added, and then the mixture is placed in an ultrasonic oscillator for 30 minutes, and 0.26 ml of 40% hydrofluoric acid is added dropwise while stirring, and the reactants are added to a reactor and placed in an oven at 220° C. for reaction for 8 hours; a green product is obtained after cooling, and solid-liquid separation is performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol are used for washing respectively until the color of the liquid does not change, and after filtration, the mixture is placed in an oven at 80° C. for drying for 8 hours to obtain a carbon capture material based on choline chloride, which is marked as n-ChCl-MIL-101(Cr), wherein n represents the concentration of choline chloride.

[0007] Wherein, the added amount of choline chloride is 0.005 mol-0.4 mol.

[0008] The choline chloride-based carbon capture material prepared by the above method is used for CO 2 Adsorption, CO 2 The adsorption breakthrough experiment includes the following steps:

[0009] S401, before starting the adsorption experiment, 1 g of n-ChCl-MIL-101(Cr) was placed in a quartz glass tube and both ends were fixed with cotton balls;

[0010] S402, use N first 2 Purge the entire pipeline until CO 2 The gas analyzer cannot detect CO 2 The adsorption experiment was started after the concentration;

[0011] S403, close the two valves entering the quartz glass tube and introduce CO 2 Gas and N 2 Gas is first calibrated by a glass rotor flowmeter and then enters a soap bubble flowmeter for secondary calibration. 2 With N 2 The flow ratio is 1:85;

[0012] S404, when the calibration is completed, open the two valves entering the glass quartz tube, close the two valves entering the soap bubble flowmeter, and start the fixed bed adsorption experiment. 2 The concentration is monitored online to obtain the CO 2 Concentration, when the outlet CO 2 Concentration and CO in the inlet mixed gas 2 End monitoring when the concentrations are the same;

[0013] S405, close the device and the entire gas path, end the adsorption experiment and draw the adsorption breakthrough curve.

[0014] Technical effects and advantages of the present invention:

[0015] The present invention studies the effect of choline chloride concentration on material structure and CO 2 The influence of the composite material on the adsorption performance was analyzed by establishing comparative samples and using adsorption experiments. 2 The results showed that with the increase of choline chloride concentration, CO 2 The variation trend of adsorption amount is volcanic. The CO of 0.075-ChCl-MIL-101(Cr) 2 The adsorption capacity is the best, and the unique pore cage structure of MIL-101(Cr) can adsorb CO well. 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is an X-ray diffraction analysis diagram of the carbon capture material prepared in the present invention.

[0017] Figure 2 This is a scanning electron microscope analysis diagram of the carbon capture material prepared in the present invention (wherein a is MIL-101(Cr), b is 0.075-ChCl-MIL-101(Cr), c is 0.1-ChCl-MIL-101(Cr), and d is 0.125-ChCl-MIL-101(Cr)).

[0018] Figure 3 N of the carbon capture material prepared in the present invention 2 Adsorption breakthrough curve diagram (where a is MIL-101(Cr), b is 0.075-ChCl-MIL-101(Cr), c is 0.1-ChCl-MIL-101(Cr), and d is 0.125-ChCl-MIL-101(Cr)).

[0019] Figure 4 This is an infrared spectrum curve of the carbon capture material prepared by the present invention.

[0020] Figure 5 This is a thermogravimetric analysis diagram of the carbon capture material prepared in the present invention (wherein a is MIL-101(Cr), b is 0.075-ChCl-MIL-101(Cr), c is 0.1-ChCl-MIL-101(Cr), and d is 0.125-ChCl-MIL-101(Cr)).

[0021] Figure 6This is a comparison chart of the adsorption amounts of the carbon capture materials prepared in the present invention (where a is MIL-101(Cr), b is 0.075-ChCl-MIL-101(Cr), c is 0.1-ChCl-MIL-101(Cr), and d is 0.125-ChCl-MIL-101(Cr)).

[0022] Figure 7 This is an elemental composition analysis diagram of the carbon capture material prepared in the present invention (wherein a is MIL-101 (Cr), b is 0.075-ChCl-MIL-101 (Cr), c is 0.1-ChCl-MIL-101 (Cr), and d is 0.125-ChCl-MIL-101 (Cr)).

[0023] Figure 8 The CO of the carbon capture material prepared by the present invention 2 Adsorption capacity analysis diagram (where a is MIL-101(Cr), b is 0.075-ChCl-MIL-101(Cr), c is 0.1-ChCl-MIL-101(Cr), and d is 0.125-ChCl-MIL-101(Cr)).

[0024] Fig. 9 This is an adsorption breakthrough curve of the carbon capture material prepared in the present invention.

[0025] Fig.10 This is an analysis diagram of the adsorption-desorption cycle of the carbon capture material prepared in the present invention.

[0026] Fig.11 It is a fitting curve diagram of the carbon capture material prepared in the present invention at different temperatures and pressures (where a is the adsorption amount of different materials under increasing pressure, and b is a comparison of the adsorption amount of 0.075-ChCl-MIL-101 at different temperatures).

[0027] Fig.12 CO 2 Schematic diagram of the adsorption breakthrough experimental setup. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] After dissolving 0.996 g of terephthalic acid in 28.6 ml of deionized water, 0.075 mole of choline chloride was added and stirred evenly, and then 2.4 g of chromium nitrate nonahydrate was added, and the mixture was placed in an ultrasonic oscillator for 30 minutes, and then 0.26 ml of 40% hydrofluoric acid was dropped while stirring, and then the reactants were added to a reactor and placed in an oven at 220° C. for reaction for 8 hours; after cooling, a green product was obtained, and the solid-liquid separation was performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol were used for multiple washings until the liquid color did not change, and then the mixture was placed in an 80° C. oven for drying for 8 hours after suction filtration, and finally the green product was placed in a sealed bag and marked as 0.075-ChCl-MIL-101 (Cr) for storage.

[0031] The crystal structures of MIL-101(Cr) and n-ChCl-MIL-101(Cr) were determined by X-ray diffractometer, and the phase analysis of the adsorbent samples was carried out, including analyzing the diffraction patterns and determining the peak positions of the samples, so as to understand the composition of the samples, the atomic or molecular structure and morphology of the samples. The X-ray diffractometer test conditions included Cu target and Kα rays, and the tube voltage and current were 40 kV and 40 mA respectively, the scanning speed was 0.5° / min, and the scanning 2θ range was 5°~80°.

[0032] The X-ray diffraction patterns of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Figure 1 As shown, compared with the standard diffraction peaks of MIL-101(Cr), the diffraction peaks 2θ of MIL-101(Cr) are 8.4°, 9.04° and 16.48°, confirming the reconstruction of MIL-101(Cr). After modification with choline chloride, the diffraction peak at 8.4° weakened, and showed a volcano-shaped trend with increasing concentration and was inversely proportional to the carbon dioxide adsorption content. The diffraction peak near 16.8° was enhanced, and showed a volcano-shaped trend with increasing concentration and was proportional to the carbon dioxide adsorption content. As the concentration increased, 0.125-ChCl-MIL-101 had a new diffraction peak at 27.5°, but its relationship with the carbon dioxide adsorption amount could not be directly determined. It was preliminarily judged that the addition of choline chloride to modify MIL-101(Cr) mainly affected the two diffraction peaks of 8.4° and 16.8°, and was inversely proportional to the increase of the diffraction peak at 8.4° and directly proportional to the increase of the diffraction peak at 16.8°, and both diffraction peaks showed a volcano-shaped trend with the concentration.

[0033] The prepared MIL-101(Cr) and n-ChCl-MIL-101(Cr) were dissolved in anhydrous ethanol and then subjected to ultrasound. The samples were then dropped onto a conductive copper plate and finally characterized after gold spraying to observe the morphological characteristics of different adsorbents.

[0034] Scanning electron microscopy images of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Figure 2 As shown. Figure 2 In (a), MIL-101(Cr) has a regular octahedral structure; Figure 2 (b) It can be seen that after the combination of the two, the skeleton structure of MIL-101(Cr) begins to change from smooth to rough because ChCl is attached to the surface of MIL-101(Cr). The crystalline morphology can also be observed from the internal pores of the enlarged 0.075-ChCl-MIL-101(Cr), which is consistent with the FT-IR analysis results. In addition, with the continuous attachment of ChCl, the uniform channels inside MIL-101(Cr) begin to fold and bend, which may be due to the fact that ChCl filling the MIL-101(Cr) channels slightly changes the surface morphology of MIL-101(Cr). Compare Figure 2 (b), (c) and (d) show that after ChCl loading, the skeleton structure of MIL-101(Cr) becomes rougher and more defective, and the curvature of its internal channels deepens, indicating that the ChCl load acts on the surface and internal channel structure of MIL-101(Cr). At the same time, the morphology of MIL-101(Cr) is also distorted and agglomerated, indicating that ChCl is also successfully loaded into MIL-101(Cr). With the increase of ChCl loading, the structure of MIL-101(Cr) becomes rougher and the distortion deepens, indicating that more ChCl molecules are filled in the pores of the MIL-101(Cr) skeleton.

[0035] N 2 Adsorption analysis is performed using N 2 Adsorption of MIL-101(Cr) and n-ChCl-MIL-101(Cr) at 77K liquid nitrogen temperature 2 The adsorption or desorption isotherms were obtained, and the samples were degassed at 100 °C for 6 h before testing.

[0036] The adsorption breakthrough curves of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Figure 3From the isotherm trend line, MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) all belong to type I isotherms, and 0.075-ChCl-MIL-101(Cr) belongs to type II isotherms. 2 The adsorption / desorption isotherms look similar but have obvious differences. From Figure (a), it can be seen that the adsorption / desorption curves are almost overlapped, proving that the adsorption / desorption process does not produce a hysteresis loop, that is, the pore structure in the adsorbent is relatively small, and there are a large number of microporous structures. Its adsorption capacity reaches 610.2472cc / g. From Figure (b), it can be seen that at about P / P 0 When the value is 0.2, there is an inflection point, which is the first steep point of the isotherm, representing the saturated adsorption of a single molecule, proving that the adsorption is complete, but the adsorption capacity still exceeds that of MIL-101(Cr) before modification, reaching 641.8073cc / g. As can be seen from Figure (c), although the 0.1mol / l choline chloride modification has the best adsorption and desorption effect on nitrogen, reaching 830.8252cc / g, but at about P / P 0 = 0.18, indicating that there are a large number of mesopores and relatively few micropores in the 0.1-ChCl-MIL-101(Cr) sample. As can be seen from Figure (d), the adsorption and desorption curves are basically overlapped, except for the P / P 0 is 0.17 and P / P 0 When the value is 0.97, a narrow hysteresis loop appears, indicating that there are a large number of mesopores and relatively few micropores, and its adsorption capacity is 582.5392cc / g.

[0037] Fourier transform infrared spectrometer was used to carry out infrared analysis of MIL-101(Cr) and n-ChCl-MIL-101(Cr). MIL-101(Cr) and n-ChCl-MIL-101(Cr) were dried and dehydrated, mixed with potassium bromide and pressed into tablets, which were fixed in a sample cell to record infrared spectra, and the wavenumber range was set to 4000cm'~500cm'.

[0038] The infrared spectra of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Figure 4 As shown. At 586cm -1 The Cr-O vibration absorption peak appears at 740cm -1 and 827cm -1 The CH vibration peak adjacent to the benzene ring appears at 1279cm-1 It is proved to be aromatic acid, at 1400cm -1 C=O vibration on symmetrical carboxylate, 1549.6 cm -1 The characteristic peak of benzene ring is at 3409cm -1 The characteristic peaks of carboxylates indicate that MIL-101(Cr) was successfully synthesized. Moreover, after adding different concentrations of ChCl, the peak at 3000 cm -1 -3400cm -1 The characteristic peaks showed large pure peaks, proving that a large number of hydroxyl groups were introduced. This result further proved the successful modification of ChCl.

[0039] The thermal stability of MIL-101(Cr) and n-ChCl-MIL-101(Cr) was analyzed by thermogravimetric analyzer, and the relationship between heat change and temperature was recorded. The heating rate of the experiment was 5°C / min, and the temperature was increased to 700°C.

[0040] The thermogravimetric curves of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Figure 5 The thermogravimetric analysis of MIL-101(Cr) mainly consists of three stages. The small amount of weight loss before 100°C is due to the larger pore cage (approximately ) releases water molecules. The weight loss at 100-200 °C is due to the escape of solvent molecules from the medium pore cage (ca. ); After 200°C, the material loses weight rapidly, and the MIL-101(Cr) framework decomposes. As the hydroxyl groups in the framework are removed, the structure begins to collapse. Therefore, MIL-101(Cr) can maintain structural stability at a temperature of about 200°C, and the mass loss is 71.71%. After adding choline chloride for modification, the thermal stability and residual mass are greatly improved. 0.075-ChCl-MIL-101(Cr) can maintain structural stability at a temperature of about 400°C, and its mass loss is 52.49%. Compared with the raw material, its residual mass increased by 59.54%. However, as the concentration of choline chloride increases, the thermal stability and residual mass begin to slowly decrease. This is because choline chloride decomposes under high temperature conditions, so the greater the concentration, the greater the mass loss, but it still exceeds its raw material.

[0041] EDS analysis utilizes incident electron beam to excite the primary x-rays of MIL-101(Cr) and n-ChCl-MIL-101(Cr), analyzes the element types according to the different wavelengths and energies of the characteristic x-rays, and determines the composition of each component in the sample material by comparing the contents of the four elements C, Cr, Cl and N.

[0042] The EDS of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are as follows: Figure 7 As shown. The final sample material after processing will lose some material during the experiment. The type and specific gravity of the characteristic elements on the surface of the material can be analyzed by energy spectrum to reflect the true composition and proportion of the material. Figure (a) shows the Cr and C elements of the typical MIL-101 (Cr) structure. Cr and Cl can be observed in Figures (b), (c), and (d), indicating that the two materials are successfully composited, which is consistent with the SEM results. In addition, combined with the content in the table, it can be seen that with the increase of the ChCl impregnation amount, the amount of ChCl actually loaded in the sample increases, which is consistent with the results of FT-IR analysis, thermal stability analysis, and SEM analysis.

[0043] The adsorption experiment was carried out on CO 2 Adsorption breakthrough experiment; specifically, CO 2 The adsorption breakthrough experiment includes the following steps:

[0044] S401, before starting the adsorption experiment, 1 g of MIL-101(Cr) or n-ChCl-MIL-101(Cr) was placed in a quartz glass tube, and both ends were fixed with cotton balls;

[0045] S402, use N first 2 Purge the entire pipeline until CO 2 The gas analyzer cannot detect CO 2 The adsorption experiment was started after the concentration;

[0046] S403, close the two valves entering the quartz glass tube and introduce CO 2 Gas and N 2 Gas is first calibrated by a glass rotor flowmeter and then enters a soap bubble flowmeter for secondary calibration. 2 With N 2 The traffic ratio is 15:85;

[0047] S404, when the calibration is completed, open the two valves entering the glass quartz tube, close the two valves entering the soap bubble flowmeter, and start the fixed bed adsorption experiment. 2 The concentration is monitored online to obtain the CO 2 Concentration, when the outlet CO 2 Concentration and CO in the inlet mixed gas 2 End monitoring when the concentrations are the same;

[0048] S405, close the device and the entire gas path, end the adsorption experiment and draw the adsorption breakthrough curve.

[0049] MIL-101 adsorbs low concentration CO 2 The adsorption experimental apparatus is as follows Fig.12 As shown in the figure, the experimental device mainly consists of four systems, namely, gas supply system, flow detection system, fixed bed adsorption system and data acquisition system. The gas supply system consists of CO 2 Gas cylinder, N 2 Gas cylinder, pressure gauge and pressure reducing valve, N 2 Used for purging pretreatment of experimental equipment, CO 2 Gas and N 2 Gas mixing, both of which are controlled by rotor flowmeter gas flow, and then corrected by soap bubble flowmeter; fixed bed adsorption system is mainly used for adsorption experiment, the fixed bed size is 5mm inner diameter, 8mm outer diameter and 120mm long high temperature resistant quartz glass tube, the adsorbent is filled in the tube; data acquisition system is CO 2 Gas analyzers, measuring CO 2 concentration.

[0050] The adsorbent was placed under vacuum at 120°C for 6 h and then the adsorption process was repeated four times. The adsorption amount was compared to determine the adsorbent stability.

[0051] The adsorption performance of n-ChCl-MIL-101(Cr) and MIL-101(Cr) under different concentrations of choline chloride modification is shown in Figure 2. Figure 8 As shown in the figure, under the same experimental conditions, the modification of MIL-101(Cr) and different concentrations of choline chloride is slightly different.

[0052] The adsorption capacities of 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) were 17.8972cc / g, 28.8487cc / g, 20.6239cc / g and 27.4263cc / g, respectively. The CO adsorption of MIL-101(Cr) modified by choline chloride at different concentrations was 2 Maximum adsorption capacity Q 0.075 >Q 0.125 >Q 0.1 >Q MIL-101(Cr) , the carbon dioxide adsorption capacity increased by 61.191%, 15.235% and 53.243% after modification. It can be inferred that its adsorption performance and carbon dioxide adsorption capacity are volcanic, and the maximum adsorption capacity is reached at a concentration of 0.075 mol / l.

[0053] The adsorption breakthrough curves of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Fig. 9 As shown in the figure, the CO 2 The adsorption penetration curves are quite similar, all changing from steep to gentle; the penetration time of MIL-101(Cr) is between 12-17min, the penetration time of 0.075-ChCl-MIL-101(Cr) is between 24-31min, the penetration time of 0.1-ChCl-MIL-101(Cr) is between 16-22min, and the penetration time of 0.125-ChCl-MIL-101(Cr) is between 22-27min. Among them, the penetration time of 0.075mol / l choline chloride modification is the longest, which means that the choline chloride modification has the best adsorption effect on carbon dioxide.

[0054] The adsorption-desorption cycles of adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) are shown in Figure 2. Fig.10 The results show that the maximum difference in adsorption capacity is less than 4%, indicating that no decomposition and loss of materials occurred during the cycle. This proves the durability of the synthetic material.

[0055] Adsorbents MIL-101(Cr), 0.075-ChCl-MIL-101(Cr), 0.1-ChCl-MIL-101(Cr) and 0.125-ChCl-MIL-101(Cr) were adsorbed at different pressures. Fig.11 (a) shows the adsorbent 0.075-ChCl-MIL-101(Cr) for CO at different temperatures. 2 The adsorption of Fig.11 (b) The results show that the equilibrium amount of carbon dioxide adsorption is inversely proportional to the temperature. This is because adsorption is usually exothermic. Therefore, as long as the adsorption equilibrium is reached, increasing the temperature will reduce the adsorption.

[0056] Using origin for fitting, the Freundlich equation can better fit the CO of the modified material than the Langmuir equation. 2 The adsorption isotherms show that the adsorption behavior of choline chloride modified materials on non-uniform surfaces is more consistent with multi-layer non-ideal adsorption behavior. The introduction of choline chloride increases the sample's adsorption to CO 2 The adsorption capacity of the composite material at a concentration of 0.075 mol / l for CO2 The adsorption effect is the best, and the adsorption saturation can reach 28.8487cc / g under the conditions of 293K and 100kPa. It is a carbon dioxide adsorbent with good application prospects. Adsorption behavior is an exothermic process, so the adsorption capacity of the material will decrease with the increase of temperature.

[0057] Example 2

[0058] 0.996 g of terephthalic acid was dissolved in 28.6 ml of deionized water, 0.1 mol of choline chloride was added and stirred evenly, then 2.4 g of chromium nitrate nonahydrate was added, and the mixture was placed in an ultrasonic oscillator for 30 min, and 0.26 ml of 40% hydrofluoric acid was added dropwise while stirring, and then the reactants were added to a reactor and placed in an oven at 220° C. for reaction for 8 h; after cooling, a green product was obtained, and the solid-liquid separation was performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol were used for multiple washings until the liquid color did not change, and the mixture was placed in an oven at 80° C. for drying for 8 h after filtration, and finally the green product was placed in a sealed bag and marked as 0.1-ChCl-MIL-101 (Cr) for storage.

[0059] Example 3

[0060] Dissolve 0.996g of terephthalic acid in 28.6ml of deionized water, add 0.125mol of choline chloride and stir evenly, then add 2.4g of chromium nitrate nonahydrate, put it in an ultrasonic oscillator and shake it for 30min, then drop 0.26ml of 40% hydrofluoric acid while stirring, then add the reactants into a reactor and put it in an oven at 220°C for reaction for 8h; after cooling, a green product is obtained, solid-liquid separation is performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol are used for multiple washings until the liquid color does not change, and then the green product is placed in a sealed bag and marked as 0.125-ChCl-MIL-101 (Cr) for storage.

[0061] Example 4

[0062] 0.996 g of terephthalic acid was dissolved in 28.6 ml of deionized water, 0.05 mol of choline chloride was added and stirred evenly, then 2.4 g of chromium nitrate nonahydrate was added, and the mixture was placed in an ultrasonic oscillator for 30 min, and then 0.26 ml of 40% hydrofluoric acid was added dropwise while stirring, and then the reactants were added to a reactor and placed in an oven at 220° C. for reaction for 8 h; after cooling, a green product was obtained, and solid-liquid separation was performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol were used for multiple washings until the liquid color did not change, and then the green product was placed in an oven at 80° C. for drying for 8 h after suction filtration, and finally the green product was placed in a sealed bag, marked as 0.05-ChCl-MIL-101 (Cr) for storage, and used for carbon dioxide adsorption (the specific method is the same as in Example 1), and the adsorption amount was 22.57 cc / g.

[0063] Example 5

[0064] 0.996g of terephthalic acid was dissolved in 28.6ml of deionized water, 0.4mol of choline chloride was added and stirred evenly, then 2.4g of chromium nitrate nonahydrate was added, and after being put into an ultrasonic oscillator for 30min, 0.26ml of 40% hydrofluoric acid was added dropwise while stirring, and then the reactants were added into a reactor and put into an oven at 220°C for reaction for 8h; after cooling, a green product was obtained, solid-liquid separation was performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol were used for multiple washings until the liquid color did not change, and after suction filtration, the product was put into an oven at 80°C for drying for 8h, and finally the green product was put into a sealed bag and marked as 0.4-ChCl-MIL-101 (Cr) for storage. It was used for carbon dioxide adsorption (the specific method is the same as in Example 1), and its adsorption capacity was 0.6cc / g.

[0065] Comparative Example 1

[0066] Dissolve 0.996g of terephthalic acid in 28.6ml of deionized water, add 2.4g of chromium nitrate nonahydrate, put it in an ultrasonic oscillator and shake it for 30 minutes, then drop 0.26ml of 40% hydrofluoric acid while stirring, and then add the reactants into a reactor and put it in an oven at 220°C for reaction for 8h; after cooling, a green product is obtained, and the solid-liquid separation is carried out by a centrifuge, and then it is washed several times with N, N-dimethylformamide and anhydrous ethanol respectively until the color of the liquid does not change, and then filtered and dried in an oven at 80°C for 8h, and finally the green product is placed in a sealed bag and marked as MIL-101 (Cr) for storage.

[0067] Comparative Example 2

[0068] Dissolve 0.996g of terephthalic acid in 28.6ml of deionized water, add 0.125mol of choline amino acid and stir evenly, then add 2.4g of chromium nitrate nonahydrate, put it in an ultrasonic oscillator and shake it for 30min, then drop 0.26ml of 40% hydrofluoric acid while stirring, then add the reactants into a reactor and put it in an oven at 220℃ for reaction for 8h; after cooling, a green product is obtained, solid-liquid separation is performed by a centrifuge, and then N, N-dimethylformamide and anhydrous ethanol are used for multiple washings until the liquid color does not change, and then the green product is placed in an 80℃ oven for drying for 8h after suction filtration, and finally the green product is placed in a sealed bag. It is used for carbon dioxide adsorption (the specific method is the same as in Example 1), and its adsorption capacity is 4.3cc / g.

Claims

1. A method for preparing a carbon capture material based on choline chloride, characterized in that: The preparation method comprises the following steps: dissolving terephthalic acid in water, adding choline chloride and stirring evenly, then adding chromium nitrate, and then placing the mixture in an ultrasonic oscillator for 30 minutes, dripping 40% hydrofluoric acid while stirring, and then adding the reactants into a reaction kettle and placing the mixture in an oven at 220° C. for reaction for 8 hours, obtaining a green product after cooling, and subjecting the product to centrifugal separation, washing, suction filtration and drying to obtain a choline chloride-based carbon capture material labeled as n-ChCl-MIL-101(Cr).

2. The method for preparing a carbon capture material based on choline chloride according to claim 1, characterized in that: The mass volume ratio of terephthalic acid, chromium nitrate and 40% concentration hydrofluoric acid is: 0.996:2.4:0.

26.

3. The method for preparing a carbon capture material based on choline chloride according to claim 1, characterized in that: The amount of choline chloride added is: 0.005 mol-0.4 mol.

4. The method for preparing a carbon capture material based on choline chloride according to claim 1, characterized in that: The product was separated by centrifuge, washed with N,N-dimethylformamide and anhydrous ethanol respectively, and dried in an oven at 80°C for 8 h.

5. A choline chloride-based carbon capture material prepared by the method according to any one of claims 1 to 4.

6. An application of a choline chloride-based carbon capture material prepared by the method according to any one of claims 1 to 4, characterized in that: The carbon capture material is used for CO2 adsorption.

Citation Information

Patent Citations

  • Degradable gas hydrate accelerant and preparation method thereof

    CN103028353A

  • Method for applying eutectic ionic liquid / metal framework material to carbon neutrality

    CN113577992A

  • Composite material for removing hydrogen sulfide, preparation method and application

    CN116651511A

  • Cu-BTC composite material for capturing carbon dioxide / hydrogen sulfide as well as preparation method and application of Cu-BTC composite material

    CN119098150A

  • Preparation method and application of marine MOF-based porous liquid carbon capture absorbent

    CN119158383A

Cited By

  • Synthesis method of MIL101

    CN121537643A